Daemons of the shadow realm. 6 - Arakawa, Hiromu, 1973- (Deamons of the shadow realm, 2024)
Having infiltrated Higashi Village and taken two of its residents hostage, Ivan beckons Yuru to a warehouse in the dead of night. Although Yuru stakes out the location from a distance, he’s swiftly kidnapped by a skull-faced Daemon under Asuma’s command. The Divine Guardians are left to fend for themselves as the familiar scents of Yuru and Asa’s parents waft from Ivan’s blood-soaked blades…